Developing mature empathy among first-year students: The learning potential of emotional experiences. (September 2018) - Konow Lund, Anne-Sophie; Heggestad, Anne Kari Tolo; Nortvedt, Per; Christiansen, Bjørg
Nursing students' ability to develop mature empathy requires emotional work, usually associated with caring experiences in relation with patients and next of kin. This article is based on qualitative in-depth interviews with 11 first-year students, and the research questions were: What characterizes situations in a nursing home that evoke strong emotional reactions in first-year students? What is the learning potential of these experiences? Findings show that facing emotionally challenging situations during their first clinical placement in nursing education aroused strong feelings and commitment among the students. The students tried, however, to find ways to handle emotionally challenging situations both with support in scientific literature, as well as from experience. Nurses were important role models, but could also exemplify characteristics of less empathic behaviour. Developing 'mature empathy' requires emotional work so that the students learn to adapt themselves to what will be demanded of them as professional nurses. The findings of this and other studies should alert nurses as well as teachers to the importance of helping students develop empathy as part of their learning trajectory in nursing education.